Deliberamos sobre la importancia de la participación ciudadana - Reaño Arana, Víctor Carlos (2023)
The present work of professional sufficiency has been planned for students of the first year of secondary education, from the city of Trujillo in the year 2022, with the theme entitled "We deliberate on the importance of democratic participation", it is evident in the work a develop ment taking into account the context in which the student lives and placing as examples, situ ations and activities that the student performs daily, remembering that we are going through democratic processes and that these will train the student to be a future citizen. In the planning of the learning session, the pedagogical processes, didactic processes to pro- mote meaningful learning taking into account the competency-based approach, were taken intoaccount. The strategies used are to promote active citizenship and taking into account the needsand interests of students.